Bangladesh politics : the Shahabuddin interregnum - Hakim, Muhammad A. (Dhaka : University Press Limited, 1993)
Political Science and Public Administration
Keywords: Politics; Parliamentary elections; Parliamentary system; Presidential election; Postscript